2019
DOI: 10.1111/ajag.12670
|View full text |Cite
|
Sign up to set email alerts
|

Help, I'm a specialist!—Perspectives of recently qualified geriatricians on the experiences and challenges of working as a consultant geriatrician

Abstract: Objective To gain insights into the experience and challenges faced by Australasian geriatricians who have recently made the transition from advanced trainee to consultant. Methods An interpretative exploratory qualitative study. Geriatricians with five or less years of experience as consultants were recruited by email. Data were collected through semi‐structured interviews, with themes identified through open axial coding. Results Respondents (n = 20) experienced a transition period in which they adjusted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…27 An Australasian study of new geriatricians recommended the creation of a ''consultant-like'' role. 28 de Montbrun et al identified 4 phases in the anxiety-provoking transition from surgical resident to attending surgeon, wherein final responsibility for patient care was suddenly assumed. 29 A study of radiation oncologists identified similar needs among trainees and junior faculty and recommended a minimally supervised longitudinal rotation for senior residents to mitigate the gap between residency and independent practice.…”
Section: Discussionmentioning
confidence: 99%
“…27 An Australasian study of new geriatricians recommended the creation of a ''consultant-like'' role. 28 de Montbrun et al identified 4 phases in the anxiety-provoking transition from surgical resident to attending surgeon, wherein final responsibility for patient care was suddenly assumed. 29 A study of radiation oncologists identified similar needs among trainees and junior faculty and recommended a minimally supervised longitudinal rotation for senior residents to mitigate the gap between residency and independent practice.…”
Section: Discussionmentioning
confidence: 99%
“…Notable examples include a recent paper examining the transition from advanced trainee to consultant, which highlighted several strategies to enhance the transition into the consultant role. 8 Similarly, a survey study of UK geriatricians' reasons for choosing the field identified implications for career development amongst junior doctors. 9 The broader health professional workplace-based learning and assessment literature contain research on how to support the learner, provide effective feedback and construct meaningful assessment processes while preparing the student for clinical practice.…”
Section: Introductionmentioning
confidence: 99%